A Dermal Piercing Complicated by Mycobacterium fortuitum. (29th August 2013) - Patel, Trisha; Scroggins-Markle, Leslie; Kelly, Brent
Abstract : Background . Dermal piercings have recently become a fashion symbol. Common complications include hypertrophic scarring, rejection, local infection, contact allergy, and traumatic tearing. We report a rare case of Mycobacterium fortuitum following a dermal piercing and discuss its medical implications and treatments. Case . A previously healthy 19-year-old woman presented complaining of erythema and edema at the site of a dermal piercing on the right fourth dorsal finger. She was treated with a 10-day course of trimethoprim-sulfamethoxazole and one course of cephalexin by her primary care physician with incomplete resolution. The patient stated that she had been swimming at a local water park daily. A punch biopsy around the dermal stud was performed, and cultures with sensitivities revealed Mycobacterium fortuitum . The patient was treated with clarithromycin and ciprofloxacin for two months receiving full resolution. Discussion . Mycobacterium fortuitum is an infrequent human pathogen. This organism is a Runyon group IV, rapidly growing nontuberculous mycobacteria, often found in water, soil, and dust. Treatment options vary due to the size of the lesion. Small lesions are typically excised, while larger lesions require treatment for 2–6 months with antibiotics. We recommend a high level of suspicion for atypical mycobacterial infections in a piercing resistant to other therapies.